1994
DOI: 10.1042/bj2980181
|View full text |Cite
|
Sign up to set email alerts
|

Molecular variants of β2-microglobulin in renal insufficiency

Abstract: Many patients with renal insufficiency treated by dialysis for more than 10 years have tissue deposits of amyloid material containing polymerized beta 2-microglobulin (beta 2m). The mechanisms of beta 2m polymerization and degradation remain unknown. In biological fluids (serum and urine) from haemodialysis patients and in dialysis fluids from patients treated by chronic ambulatory peritoneal dialysis (CAPD), we have characterized different molecular forms of beta 2m, including proteolytic split products. beta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…Trefoil factor‐3 and thrombomodulin have been reported as sensitive markers of early and reversible renal injury . β‐2 microglobulin is the light chain of major histocompatibility complex expressed on all nucleated cells and, like α‐1 microglobulin and cystatin C, is filtered by the glomerulus and reabsorbed/catabolized by the proximal tubule . Similar to our findings, a recent nontransplant study found associations between β‐2 microglobulin, cystatin C, and future CKD, even in patients with baseline eGFR >60 mL/min/1.73 m 2 .…”
Section: Discussionsupporting
confidence: 89%
“…Trefoil factor‐3 and thrombomodulin have been reported as sensitive markers of early and reversible renal injury . β‐2 microglobulin is the light chain of major histocompatibility complex expressed on all nucleated cells and, like α‐1 microglobulin and cystatin C, is filtered by the glomerulus and reabsorbed/catabolized by the proximal tubule . Similar to our findings, a recent nontransplant study found associations between β‐2 microglobulin, cystatin C, and future CKD, even in patients with baseline eGFR >60 mL/min/1.73 m 2 .…”
Section: Discussionsupporting
confidence: 89%
“…Apart from the large amount of β 2 m fibrils, amyloid plaques isolated from DRA patients contain proteolytic β 2 m fragments 5, 6, 11, 6166. These fragments can act as seeds accelerating amyloid aggregation 11, 12, 14.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is hypothesized that native β2m undergoes some modifications, becoming a modified β2m with possible more amyloidogenesis. Several novel β2ms have been found, one being acidic β2m [2, 3, 4, 5]. Among them, β2m modified with advanced glycation end products (AGEs) have been reported to be involved in the pathogenesis of DRA [6 , 7].…”
Section: Introductionmentioning
confidence: 99%